2009
DOI: 10.1038/sc.2009.145
|View full text |Cite
|
Sign up to set email alerts
|

Medication use is associated with fatigue in a sample of community-living individuals who have a spinal cord injury: a chart review

Abstract: Objectives: To investigate the relationship between medications known to cause fatigue in spinal cord injury (SCI) and fatigue severity and to describe the pattern of prescription of these medications. Results: Fifty-two percent of the subjects had clinically relevant fatigue. As a group, the subjects were taking 147 different medications; 41/147 medications were identified as causing fatigue. The two most commonly prescribed categories of medications were antispasticity medications (75 subjects) and analgesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 13 publications
5
32
0
Order By: Relevance
“…According to our results, the daily intake of a number of antihypertensives, analgesics and medications for spasticity, probably affects PF, but to a small degree the mental dimensions of fatigue in persons with longstanding SCI. The findings support Lee et al 10 who also found that usage of a number of analgesics was statistically significantly contributing to higher fatigue scores as measured with the Fatigue Severity Scale. However, the Fatigue Severity Scale (unidimensional scale) does not distinguish mental and physical dimensions of fatigue.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…According to our results, the daily intake of a number of antihypertensives, analgesics and medications for spasticity, probably affects PF, but to a small degree the mental dimensions of fatigue in persons with longstanding SCI. The findings support Lee et al 10 who also found that usage of a number of analgesics was statistically significantly contributing to higher fatigue scores as measured with the Fatigue Severity Scale. However, the Fatigue Severity Scale (unidimensional scale) does not distinguish mental and physical dimensions of fatigue.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, some of the above mentioned variables have shown relationships to fatigue. [8][9][10] As previously mentioned, the variability of findings among studies may be related to methodological differences, and need further clarification.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…4 Such medications can cause adverse effects on their own with risk of adverse reactions increasing when combined with other medications, potentially leading to interference with rehabilitative efforts and daily activities. Recent research reports medications for pain and spasticity to be associated with increased risk of fatigue and falls, [5][6][7] whereas psychotropic medications have been associated with reduced life expectancy in individuals with SCI. 8 Predicting the possibility of adverse drug effects is more challenging in SCI because drug pharmacokinetics can be altered following the injury and the degree of alteration can vary depending on the level and severity of SCI.…”
Section: Introductionmentioning
confidence: 99%